On a long, narrow road: The mental health law in Turkey - Artvinli, Fatih; Uslu, Merve Kardelen Bilir (PERGAMON-ELSEVIER SCIENCE LTD, 2023)
This article presents the historical transformation of the mental health system and policies in the case of Turkey and discusses the challenges to their effective implementation. The mental health system in Turkey has undergone a series of reforms in three periods, namely, the institutionalization of psychiatry and hospital-based mental health services in the mid-19th century, the introduction of first-generation community-based mental healthcare services in the 1960s, and the policy of deinstitutionalization after the 1980s. In this transformation process, certain initiatives have been implemented with the participation of interested actors across periods and small but important improvements. A draft has been prepared after a series of studies were conducted with regard to mental health policies and plans. However, no results have been obtained. The necessity of the mental health law has been clear. A notion that has been known is that the mental health law, which offers a holistic perspective, positively influences the functioning of the mental health system in terms of service users and providers. However, whether or not it actually pursues these intended improvements has been subject to doubt. Until now, no mental health law has been effectively implemented in Turkey, and measuring and evaluating in which aspects the law will be successful and where it will fail have been impossible. Turkey continues to be in need of a mental health law is practical and in line with international standards for the rights of patients and supervision against coercive measures.
Keywords: Psychiatric system; Mental health law; Mental health system; Mental health policy; Turkey; LEGISLATION; INVOLUNTARY; CONVENTION; COMMUNITY; EUGENICS; MEDICINE; SERVICES; RIGHTS; CARE; Government & Law; Psychiatry